2006
DOI: 10.1111/j.1532-5415.2006.00701.x
|View full text |Cite
|
Sign up to set email alerts
|

Meaningful Change and Responsiveness in Common Physical Performance Measures in Older Adults

Abstract: Best initial estimates of small meaningful change are near 0.05 m/s for gait speed, 0.5 points for SPPB, and 20 m for 6MWD and of substantial change are near 0.10 m/s for gait speed, 1.0 point for SPPB, and 50 m for 6MWD. For clinical use, substantial change in these measures and small change in gait speed and 6MWD, but not SPPB, are detectable. For research use, these measures yield feasible sample sizes for detecting meaningful change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

95
1,609
33
17

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,989 publications
(1,808 citation statements)
references
References 28 publications
95
1,609
33
17
Order By: Relevance
“…In an unadjusted model, the difference in gait speed after 3 years of follow-up was significant and in an adjusted model, this difference did not reach statistical significance, but remained clinical relevant (− 0.07 m/s) according the smallest meaningful change estimate by Perera et al (− 0.05 m/s) (Perera et al 2006).…”
Section: Discussionmentioning
confidence: 79%
“…In an unadjusted model, the difference in gait speed after 3 years of follow-up was significant and in an adjusted model, this difference did not reach statistical significance, but remained clinical relevant (− 0.07 m/s) according the smallest meaningful change estimate by Perera et al (− 0.05 m/s) (Perera et al 2006).…”
Section: Discussionmentioning
confidence: 79%
“…Previous studies reported clinically meaningful changes in walking speed in community-dwelling older adults for the 4-m walking test of 0.12 m/s (Perera et al 2006). More in general, small and substantial clinically meaningful changes in walking speed were reported from 0.05 to 0.10 m/s, respectively (Bohannon and Glenney 2014;Perera et al 2006). In this study, we found differences in walking speeds of 0.11 m/s for the 10-m compared to the 4-m walking test and 0.06 m/s for the 10-m compared to the 6-min walking test.…”
Section: Discussionmentioning
confidence: 96%
“…Although the differences in physical performance measures between weight status groups were modest, they are at levels demonstrated to be clinically meaningful. 33,34 Perera et al 33 demonstrated that a change of 0.5 points on the original SPPB (range of 0-12 20 ) represents a small meaningful change, while a change of 1.0 points represents a substantial meaningful change. This would be equivalent to approximately a difference of 0.16 and 0.33 points, respectively, on the Health ABC SPPB.…”
Section: Discussionmentioning
confidence: 99%